Differences analysis in situational efficiency of winners and defeated fighters at the international boxing tournament - Kapo, S.; Fetahovic, D.; Cutuk, H.; Zoranic, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Success in boxing is defined by the level and structure of a large number of abilities, knowledge, and characteristics which can be measured and analyzed, and then improved during the sports carrier with adequate means and methods (Kapo, 2005). Main goal is identification of parameters of situational efficiency of fighters based on the registration of events during a tournament, using a set of technical and tactical elements applied by winners and defeated fighters at the boxing tournament "Zlaten Gong 2010" in Skopje. Methods: The sample of analyzed fighters comprised of 56 representative competitors. The information was gathered based on video records of 28 fights / 18 semi-final and 10 final fights/. The collected data were processed using descriptive statistics. Results and discussion: The basic descriptive parameters indicate that the total frequency of punches at this boxing tournament was 4,269, or 53.2%, for the winners, while for the defeated fighters it was 3,755, or 46.8%, of the total number of applied hand technical elements during fights. The winners were dominant in the application of direct punches to the head, with 2,682, or 63%, while the defeated fighters had only a somewhat higher frequency of applied uppercut punches to the head, namely 157, or 4%. The application of defensive techniques is on the side of defeated fighters, with a total frequency of 1,949, or 53%, while winners had a frequency of 1,665, or 47%. The winners applied a larger number of defense techniques against uppercut punches, 285 or 8%, than the defeated fighters, most probably due to the reason that the defeated fighters more frequently applied uppercut punches. The frequency of used offensive tactics and attacking techniques by the winners was 15, or 26.7%, which most probably contributed to their win, while the defeated fighters used defensive and combined tactics, which is confirmed by the fact that they applied defensive techniques more often than offensive techniques. A significant frequency of knock-downs was displayed by winners, namely 13, or 93%, while the defeated fighters only had one knock-down, or 7%, at the tournament. Conclusion: The analysis of the differences in application of technical and tactical elements between the winners and defeated boxers, indicate that the winners used all hand techniques, and applied mostly offensive tactics, more than the defeated boxers.